Pre- Service English Teachers’ Challenges and Opportunities in Flex Model Blended Learning -Assisted: Narrative Inquiry - Abdurahman, Naufal Daffa; Bani Ahmad, Yoesef (English Language Teaching for EFL Learners Journal, 2023)
Hybrid or blended learning is an alternative method during Covid-19 Pandemic. In this context, flex model blended learning is one of the ways for handling teaching and learning processes because it can be done without face-to-face interaction. This narrative research aims to investigating the challenges and opportunities of pre-service English teacher in implementing flex model on blended learning teaching. The data was collected through interview. This research was conducted to five Pre-service’s English teachers at University in Karawang who conduct online teaching in various public schools. The findings revealed that there are some challenges and opportunities appeared while implementing flex model blended learning. The challenges were low media utilization, low connectivity, disordered time allocation and low student interaction. Furthermore, the opportunities of flex model blended learning were resources and flexibility. This research is expected to help pre-service’s English teacher, English teachers, student and school to be better in implementing flex model blended learning.